Coastal Ecosystem-Features, Constraints and Future Suggestions: An Overview - SEN, H S (Journal of the Indian Society of Coastal Agricultural Research, 2019)
Coastal ecosystem poses a delicate equilibrium between land and water masses amongst its different components but with high degree of vulnerability in spite of bountiful natural resources. The equilibrium is further under serious threat due to climate change and global warming. On the other hand, it is significant that coastal marshes tend to sequester carbon continuously with increasing storage capacity and with time, and thus regarded as a valuable C sink per unit area, particularly in the tropics, to negate adverse impacts due to global warming. Planning for effective and sustainable development warrants specific attention to maintain the equilibrium. This will require adoption of integrated approach to soil and water management, in the first place, and through it or otherwise, necessary measures to conserve the ecology. Piecemeal approaches to reclaim location specific problems or interference with the hydrology of the rivers per se for short term gains for increase of productivity or otherwise, disregarding completely the practices on integrated management of different intervention areas and thereby conserve the ecology in coastal plains, may offset the equilibrium, as experienced in different parts of the world, leading to such adverse impacts, such as seawater intrusion into inland areas, massive loss of mangroves, coral reefs, seagrasses and various other aquatic plant & animal species, sedimentation & erosion, tidal flooding, subsidence of land, etc. The influx of reckless application with fast increasing dose of nitrogen or other inputs resulting in nutrient imbalance through human activities in the adjoining inland and coastal areas are glaring examples leading to such phenomena as eutrophication and formation of dead-end zones in the coastal water bodies. Policy approach for water budgeting of different water resources, preferably on watershed basis, with minimal or planned dependence on abstraction of the underground water should be an essential strategy to be drawn in order to ensure sustainable increase in crop water productivity as well as water productivity in other sectors all along the coast. It is emphasized that GoI has the scope to develop more comprehensive climate change policies to mitigate weather adversities causing colossal loss due to impacts of the natural disasters. There is a need for development and validation of location specific rice-based diversified farming models for both east and west coasts of the country. These models should be cost-effective and environmentally sustainable and can optimize utilization of natural and human resources. Dissemination of rice-based farming systems will need support facilities in terms of capacity building, partnership development, market intelligence and micro-finance. It is strongly urged to explore and exploit non-farm actions, be it ecotourism or beyond, seriously, alongside application of on-farm activities, to improve livelihood sustainably with full protection to ecology of the area in the coastal ecosystem.